1998
DOI: 10.1016/s0008-6363(98)00002-9
|View full text |Cite
|
Sign up to set email alerts
|

L-type calcium current in human ventricular myocytes at a physiological temperature from children with tetralogy of Fallot

Abstract: The present study demonstrates that most of the electrophysiological properties of ICa,L in ventricular myocytes isolated from children with tetralogy of Fallot resemble those of adult ventricular cells. The existence of a big calcium window current could be involved in the occurrence of early afterdepolarizations which could lead to the high incidence of arrhythmias after surgical repair of tetralogy of Fallot.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 39 publications
5
35
0
Order By: Relevance
“…Figure 1b shows the different current-voltage curves, where it can be observed that the new definition of I CaL is in good agreement with the available experimental data [14][15][16], with the additional benefit of contributing to physiological model response in terms of S1S2 APD 90 restitution and APD 90 rate adaptation dynamics.…”
Section: (I) the Gpb Modelsupporting
confidence: 72%
See 1 more Smart Citation
“…Figure 1b shows the different current-voltage curves, where it can be observed that the new definition of I CaL is in good agreement with the available experimental data [14][15][16], with the additional benefit of contributing to physiological model response in terms of S1S2 APD 90 restitution and APD 90 rate adaptation dynamics.…”
Section: (I) the Gpb Modelsupporting
confidence: 72%
“…where Frdy is Faraday's constant, FoRT is the ratio between Faraday's constant and the product of the gas constant and the absolute temperature,Ī k m is the maximal current for ion k in the compartment m, and p k is the relative permeability of ion k. The current-voltage curve obtained with the new definition of the I CaL current was compared with the experimental data [14][15][16] and with the original definition of the GPB model. Figure 1b shows the different current-voltage curves, where it can be observed that the new definition of I CaL is in good agreement with the available experimental data [14][15][16], with the additional benefit of contributing to physiological model response in terms of S1S2 APD 90 restitution and APD 90 rate adaptation dynamics.…”
Section: (I) the Gpb Modelmentioning
confidence: 99%
“…Additional studies into drug antagonism of these ion channels have further shown that the current density and activation properties of the channels for INa, ICa, IKr, IKs, IKr, IKi, If and Ito in hiPSC-CMs (Moretti et al, 2010;Ma et al, 2011) are quantitatively similar to those in human cardiomyocytes (Sakakibara et al, 1993;Feng et al, 1996;Pelzmann et al, 1998;Jost et al, 2009).…”
Section: Figurementioning
confidence: 94%
“…3, A and B). ICaL voltage-clamp experiments indicate the presence of both a fast and slow voltage-dependent recovery process (32,35,46). Therefore, we incorporate both a slow voltage inactivation gate f and a fast voltage inactivation gate f 2, similar to the approach taken by Hund and Rudy (19).…”
Section: Model Developmentmentioning
confidence: 99%